If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying t + 75 = 4t Reorder the terms: 75 + t = 4t Solving 75 + t = 4t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-4t' to each side of the equation. 75 + t + -4t = 4t + -4t Combine like terms: t + -4t = -3t 75 + -3t = 4t + -4t Combine like terms: 4t + -4t = 0 75 + -3t = 0 Add '-75' to each side of the equation. 75 + -75 + -3t = 0 + -75 Combine like terms: 75 + -75 = 0 0 + -3t = 0 + -75 -3t = 0 + -75 Combine like terms: 0 + -75 = -75 -3t = -75 Divide each side by '-3'. t = 25 Simplifying t = 25
| b+9=4b | | -11+5x=4+6x | | 2(4x-3)-8=4(4-2x) | | s+81=2s | | -20h=-7(4h+20)-12 | | 90-2x=-5+3x | | x-40=-5x+50 | | -2.25(x-1.5)(x-6)=0 | | b+28=5b | | c+13=2c | | -x+0.25y-s=-1.75 | | -3x-14=-6x+25 | | 17.5g+8.29=-2(-11.1g-18.48) | | -16+36=-4(x+9) | | (X-4)(x-4)=44 | | 8x-11=5x+11 | | 6(2n+3)=8(5n+2)+3 | | -3(7b+15)=9-18b | | (5-7i)(3-8i)=0 | | 11-15x-7-6x=7 | | 6+26=-4(2x-8) | | -72+5x=-6x+27 | | -19.4m=-7m-4(3m+17.83) | | 11+1=-4(9x-3) | | 13+2(5c*2)=29 | | -2x-13=-5+5 | | 0=.25x+40 | | -16+12w=7+5+10w | | -6x-13=17-x | | 4(2x+7)=-23+43 | | 4x-(5-x)=35 | | 7(2n+3)=7(7n+5)+5 |